Angiotensin II Stimulates Thick Ascending Limb NO Production via AT(2) Receptors and Akt1-dependent Nitric-oxide Synthase 3 (NOS3) Activation - Herrera, Marcela (American Society for Biochemistry and Molecular Biology, 2010)
Angiotensin II (Ang II) acutely stimulates thick ascending limb (TAL) NO via an unknown mechanism. In endothelial cells, activation of Ang II type 2 receptor (AT(2)) stimulates NO. Akt1 activates NOS3 by direct phosphorylation. We hypothesized that Ang II stimulates TAL NO production via AT(2)-mediated Akt1 activation, which phosphorylates NOS3 at serine 1177. We measured NO production by fluorescence microscopy. In isolated TALs, Ang II (100 nm) increased NO production by 1.1 ± 0.2 fluorescence units/min (p < 0.01). Ang II increased cGMP accumulation by 4.9 ± 1.3 fmol/μg (p < 0.01). Upon adding the AT(2) antagonist PD123319 (1 μm), Ang II failed to stimulate NO (0.1 ± 0.1 fluorescence units/min; p < 0.001 versus Ang II); adding the AT(1) antagonist losartan (1 μm) resulted in Ang II stimulating NO by 0.9 ± 0.1 fluorescence units/min. Akt inhibitor (5 μm) blocked Ang II-stimulated NO (−0.1 ± 0.2 fluorescence units/min versus inhibitor alone). Phospho-Akt1 increased by 72% after 5 min (p < 0.006), returning to basal after 10 min. Phospho-Akt2 did not change after 5 min but increased by 115 and 163% after 10 and 15 min (p < 0.02). Phospho-Akt3 did not change. An AT(2) agonist increased pAkt1 by 78% (p < 0.02), PI3K inhibition blocked this effect. In TALs transduced with dominant negative Akt1, Ang II failed to stimulate NO (0.1 ± 0.2 fluorescence units/min versus 1.2 ± 0.2 for controls; p < 0.001). Ang II increased phospho-NOS3 at serine 1177 by 130% (p < 0.01) and 150% after 5 and 10 min (p < 0.02). Ang II increased phosphoNOS3 at serine 633 by 50% after 5 min (p < 0.01). Akt inhibition prevented NOS3 phosphorylation. We concluded that Ang II enhances TAL NO production via activation of AT(2) and Akt1-dependent phosphorylation of NOS3 at serines 1177 and 633.